Buying time: a rationale for examining the use of circadian rhythm and sleep interventions to delay progression of mild cognitive impairment to Alzheimer’s disease - Landry, Glenn J.; Liu-Ambrose, Teresa (Frontiers in Aging Neuroscience, 2014)
As of 2010, the worldwide economic impact of dementia was estimated at $604 billion USD; and without discovery of a cure or effective interventions to delay disease progression, dementia’s annual global economic impact is expected to surpass $1 trillion USD as early as 2030. Alzheimer’s disease (AD) is the leading cause of dementia accounting for over 75% of all cases. Toxic accumulation of amyloid beta (AB), either by overproduction or some clearance failure, is thought to be an underlying mechanism of the neuronal cell death characteristic of AD – though this amyloid hypothesis has been increasingly challenged in recent years. A compelling alternative hypothesis points to chronic neuroinflammation as a common root in late-life degenerative diseases including AD. Apolipoprotein-E (APOE) genotype is the strongest genetic risk factor for AD: Individuals with APOE-e4 genotype accumulate more AB, are at high risk of developing AD, and almost half of all AD patients have at least one e4 allele. Recent studies suggest a bidirectional relationship exists between sleep and AD pathology. Sleep may play an important role in AB clearance and getting good quality sleep versus poor quality sleep might reduce the AD risk associated with the e4 allele. Taken together, these findings are particularly important given the sleep disruptions commonly associated with AD and the increased burden disrupted sleep poses for AD caregivers. The current review aims to: 1) Identify individuals at high risk for dementia who may benefit most from sleep interventions; 2) Explore the role poor sleep quality plays in exacerbating AD type dementia; 3) Examine the science of sleep interventions to date; and 4) Provide a road map in pursuit of comprehensive sleep interventions, specifically targeted to promote cognitive function and delay progression of dementia.